2020
DOI: 10.1111/jace.17566
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal stability of the lepidocrocite‐type titanates by intercalation of large alkaline ions

Abstract: The layered oxides demonstrate a lower thermal conductivity than their non-layered counterpart materials. 1,2 The thermal conductivity of the layered oxides has a strong anisotropy. For example, Bi 2−x Pb x Sr 2 Co 2 O y (x = 0, 0.4, and 0.6) has an out-of-plane thermal conductivity of 0.4 W/m K at room temperature (RT), 3 while its in-plane thermal conductivity is up to 3.5 W/m K. 4 Interestingly, Shen Y et al reported that the low thermal conductivity of layered Bi 4 Ti 3 O 12 persisted up to at least 1000°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The basal spacings of Li-ILT, Na-ILT, K-ILT, and Cs-ILT are calculated by using the position of the (020) peak, and their values are 0.68, 0.71, 0.76, and 0.85 nm at angles of 12.9, 12.4, 11.6, and 10.4°, respectively. These data are similar to our previous findings . The interlayer distance changes from 0.68 to 0.85 nm as the size of the interlayer ion increases.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The basal spacings of Li-ILT, Na-ILT, K-ILT, and Cs-ILT are calculated by using the position of the (020) peak, and their values are 0.68, 0.71, 0.76, and 0.85 nm at angles of 12.9, 12.4, 11.6, and 10.4°, respectively. These data are similar to our previous findings . The interlayer distance changes from 0.68 to 0.85 nm as the size of the interlayer ion increases.…”
Section: Resultssupporting
confidence: 92%
“…The interlayer distance changes from 0.68 to 0.85 nm as the size of the interlayer ion increases. The diffraction peak at 10.4° marked by a dot in Na-ILT is due to its swollen phase . Sasaki et al also noticed the swollen phase of Na-ILT and suggested that the swollen phase is responsible for the formation of a bilayer hydrate, as opposed to other monolayer hydrates …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed result contrasts with phase transformations in K 2 Ti 4 O 9 , β-Li 2 TiO 3 , and H 2 Ti 3 O 7 , suggesting that the interlayer ion exerts a secondary effect to the Ti–O interactions, which prohibit/catalyze the phase change. This effect is well known for H + where the interlayer OH group leads to lower thermal stability in protonic titanate. ,, After Cs + deintercalation, the system can achieve charge neutrality by (i) H + (or most likely H + ·H 2 O) intercalation, (ii) slight oxidation state increase to Ti 4+δ , and (iii) oxygen vacancy formation. Note that (i) will preserve the SCD, while (ii) and (iii) will decrease the SCD.…”
Section: Resultsmentioning
confidence: 92%
“…This effect is well known for H + where the interlayer OH group leads to lower thermal stability in protonic titanate. 11,29,60 After Cs + deintercalation, the system can achieve charge neutrality by (i) H + (or most likely H + •H 2 O) intercalation, (ii) slight oxidation state increase to Ti 4+δ , and (iii) oxygen vacancy formation. Note that (i) will preserve the SCD, while (ii) and (iii) will decrease the SCD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%